Modifikasi Perilaku Dalam Proses Adaptasi Warga Binaan Baru Di Lembaga Pemasyarakatan Pemuda Kelas IIA Tangerang - Ridho Hidayat; Moh. Amin Tohari (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This research aims to determine behavior modification in the adaptation process, and the obstacles to the adaptation process for new inmates at the Class IIA Tangerang Penitentiary. Type of qualitative descriptive research to obtain in-depth data. The collection technique is carried out by random interviews, collecting actual information in detail, identifying problems and collecting data from in-depth interviews, observation and documentation. Informant research, namely only 5 (five) people from the research subjects were selected and considered to represent the whole, determining the data source for the people interviewed, namely, there were two types of key informants and main informants. The data analysis method is by describing or explaining the phenomena resulting from observation or interview activities, explained in the form of words, sentences or images. with researchers using the triangulation method by comparing checking the validity of data obtained from observations, interviews and documentation studies. Based on the data found in the field in correctional institutions that are experienced by new inmates, namely the adaptation stage, there are 4 processes in adapting, namely Honeymoon, culture shock, adjustment. New inmates don't feel happy, but rather anxiety such as stress, depression, fear of being bullied or even sick, behavior modification in correctional institutions carries out stages, namely socialization development, spiritual development and independence development, from the stage that institutions for inmates no longer experience anxiety and can accept the environment new and don't feel stressed to the point of getting sick. Changes in the behavior of new inmates have undergone changes, namely they have followed spirituality and participated in programs within correctional institutions so that they do not experience stress and depression. From the researchers' conclusions, the inmates will no longer repeat their actions, namely their strong desire to change and of course the coaches in correctional institutions who always provide positive values to new inmates.